Activated Kras and Ink4a/Arf deficiency cooperate to produce metastatic pancreatic ductal adenocarcinoma - Aguirre, Andrew J. (Cold Spring Harbor Laboratory Press, 2003)
Pancreatic ductal adenocarcinoma ranks among the most lethal of human malignancies. Here, we assess the cooperative interactions of two signature mutations in mice engineered to sustain pancreas-specific Cre-mediated activation of a mutant Kras allele (Kras(G12D)) and deletion of a conditional Ink4a/Arf tumor suppressor allele. The phenotypic impact of Kras(G12D) alone was limited primarily to the development of focal premalignant ductal lesions, termed pancreatic intraepithelial neoplasias (PanINs), whereas the sole inactivation of Ink4a/Arf failed to produce any neoplastic lesions in the pancreas. In combination, Kras(G12D) expression and Ink4a/Arf deficiency resulted in an earlier appearance of PanIN lesions and these neoplasms progressed rapidly to highly invasive and metastatic cancers, resulting in death in all cases by 11 weeks. The evolution of these tumors bears striking resemblance to the human disease, possessing a proliferative stromal component and ductal lesions with a propensity to advance to a poorly differentiated state. These findings in the mouse provide experimental support for the widely accepted model of human pancreatic adenocarcinoma in which activated KRAS serves to initiate PanIN lesions, and the INK4A/ARF tumor suppressors function to constrain the malignant conversion of these PanIN lesions into lethal ductal adenocarcinoma. This faithful mouse model may permit the systematic analysis of genetic lesions implicated in the human disease and serve as a platform for the identification of early disease markers and for the efficient testing of novel therapies.